The Relationship Between Earnings Quality and Corporate Governance of Software and Information Technology Service Industry in China - ZHANG, MEILIN (2020)
With the development of China's capital market, many listed companies have emerged, especially the development of software and information technology industry. Therefore, the earnings information disclosed by enterprises and the earnings quality of enterprises are very important because it is the basis that investors can refer to when investing. At the same time, effective corporate governance is conducive to establish a reasonable and scientific company strategic decision making, implementation and supervision system. Therefore, the purpose of this paper is to research and analyse the relationship between earnings quality and corporate governance in China's software and information technology (IT) service industry.